2000
DOI: 10.1038/sj.jhh.1001112
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transcutaneous electric nerve stimulation in patients with therapy-resistant hypertension

Abstract: Objectives: Afferent nerve stimulation, such as acupuncture and transcutaneous electric nerve stimulation (TENS), has shown a blood pressure reduction in both animal and man. In the present open and non-controlled study we investigated the effect on 24-h ambulatory blood pressure of low frequency TENS in a group of hypertensive subjects who do not respond properly to pharmacological treatment. Method: Twelve patients were investigated. The patients were treated with TENS at two acupoints on both forearms for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
1
26
0
1
Order By: Relevance
“…For healthy subjects, low-frequency TENS reduced sympathetic and increased parasympathetic modulation; however, at high frequencies, these results were the opposite (10). In this regard, the chronic application of low-frequency TENS reduced arterial systolic and diastolic pressure in hypertensive patients (11,12). However, recent studies have demonstrated that, at low frequency, TENS did not modify the values of systemic arterial pressure in normotensive (32) and hypertensive volunteers (13).…”
Section: Discussionmentioning
confidence: 98%
“…For healthy subjects, low-frequency TENS reduced sympathetic and increased parasympathetic modulation; however, at high frequencies, these results were the opposite (10). In this regard, the chronic application of low-frequency TENS reduced arterial systolic and diastolic pressure in hypertensive patients (11,12). However, recent studies have demonstrated that, at low frequency, TENS did not modify the values of systemic arterial pressure in normotensive (32) and hypertensive volunteers (13).…”
Section: Discussionmentioning
confidence: 98%
“…This interaction of TENS with the cardiovascular system is demonstrated by vasodilation (Cramp et al, 2000;Miller, Gruben, & Morgan, 2000;Sherry et al, 2001;Vieira et al, 2012), increased blood in peripheral and coronary blood flow (Chauhan et al, 1994;Jessurun et al, 1998;Cramp et al, 2000;Miller et al, 2000;Sandberg, Sandberg, & Dahl, 2007), decreased peripheral vascular resistance (Mannheimer, Emanuelsson, & Waagstein, 1990;Sherry et al, 2001), and heart rate (Nitz, 2003). The combination of these mechanisms reduces the blood pressure demonstrated in healthy volunteers (Sherry et al, 2001;Nitz, 2003;Vieira et al, 2012) and in hypertensive patients (Kaada et al, 1991;Jacobsson et al, 2000). Previous studies have demonstrated the therapeutic potential of TENS (70 Hz) in patients with severe coronary artery disease, in which the application on the chest region showed decreased angina pectoris crisis, reduced circulating levels of epinephrine and norepinephrine (Mannheimer et al, 1990;Chauhan et al, 1994), attenuation of ST segment depression (Mannheimer et al, 1985), reduced systolic blood pressure (Mannheimer et al, 1990) and nitroglycerin consumption (Mannheimer et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…TENS is presented as a potential non-pharmacological resource that can be applied in the management of some cardiovascular diseases, such as hypertension (Chauhan et al, 1994;Cramp, Gilsenan, Lowe, & Walsh, 2000;Raimundo et al, 2009;Stein et al, 2011). Previous studies have demonstrated that TENS application reduced the systemic blood pressure of healthy volunteers (Sherry, Oehrlein, Hegge, & Morgan, 2001;Nitz, 2003;Vieira et al, 2012) and hypertensive patients (Kaada, Flatheim, & Woie, 1991;Jacobsson, Himmelmann, Bergbrant, Svensson, & Mannheimer, 2000). However, these results have not been confirmed by other studies (Lazarou & Athanasios, 2009), thus its application is still questionable in this clinical condition.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several recent review publications have expressed concern regarding the lack of controls and the potential for placebo effects in prior studies, and have made several pertinent suggestions for improving future studies [26]. Improvements for future study of acupuncture in hypertension include 24-h ambulatory BP monitoring to obtain a more accurate recording of the dynamic 24 h changes in BP [27].…”
Section: Limitations Of Previous Clinical Acupuncture Researchmentioning
confidence: 97%